The halal wave - Anmol Khan Rai (2019)
Islam is set to be the largest religion globally in the next century, based on a study by Pew Research Center. With that, the number of Muslims are expected to reach 3 billion by 2060, creating a surge in demand for halal and Muslim-friendly products. Trillions of dollars are spent by Muslims worldwide and businesses are increasingly catering to their needs.